THE ROLE OF ART THERAPY IN SCHOOLS: UNDERSTANDING THE CONTEXT, PRACTICE, AND EVIDENCE - Said Aissaoui,; Samia Djemai, (International Journal of Innovative Technologies in Social Science, 2024)
The role of art therapy in schools is investigated in this article, encompassing its background, techniques, and supporting evidence. This research, based on an initial review of scientific literature and prior studies, concentrates on the effects of art therapy in elementary schools, particularly in the context of global events like the pandemic that affect mental well-being. The results show the effectiveness of art therapy in treating a wide range of psychological and behavioral issues in children, including anxiety, depression, and ADHD. The presentation also highlights the role of art therapy in improving scholars’ social and emotional skills and academic performance. The research recommends integrating art therapy programs into educational institutions as an essential part of mental health support systems.